Knowledge, attitudes, and practices of health care professionals regarding dengue fever: need for training and provision of diagnostic equipment in Togo in 2022, a cross-sectional study - Togan, Roméo Mèdéssè; Diallo, Amadou Ibra; Zida-Compaoré, Wendpouiré Ida Carine; Ba, Mouhamadou Faly; Sadio, Arnold Junior; Konu, Rodion Yao; Bakoubayi, Akila Wimima; Tchankoni, Martin Kouame; Gnatou, Gatibe Yendu-Suglpak; Gbeasor-Komlanvi, Fifonsi Adjidossi; Diongue, Fatoumata Binetou; Tine, Jean Augustin Diégane; et al. (Frontiers in Public Health, 2024)
Health statistics on dengue are virtually non-existent, despite the fact that the virus is circulating in Togo. This study aimed to assess the knowledge, attitudes, and practices (KAP) of health professionals in the Kara health region.A cross-sectional study was conducted from March to June 2022 among healthcare professionals who had worked in the Kara region of northern Togo were selected using an exhaustive recruitment method. Data were collected by trained resident doctors with a face-to-face interview using a standardized, pretested questionnaire based on the WHO 2009 dengue guide. Three multivariate regression models were utilized to investigate factors associated with knowledge, attitudes and, and practices.A total of 464 respondents (37,1% female), median age 35years, interquartile range (29-43 years) were included. Only (3.0%) of the participants had received training on dengue fever diagnosis, treatment and prevention in the last three years, and 10.3% had dengue rapid diagnostic tests available at their hospital. Half of the respondents (49.1%) had good knowledge of dengue fever, compared with 30.0% who had positive attitudes. Of a total of 256 professionals who had encountered a case of dengue fever in their practice, only 24 (9.4%) had appropriate practices for diagnosing and treating dengue fever. In multivariate analysis, the healthcare professionals who had taken part in ongoing training on dengue fever were more likely to have adequate dengue diagnosis and treatment practice aOR = 8.1; CI 95% = [1.7-36.0].Strengthening healthcare professionals' dengue-related skills through ongoing training and the provision of dengue diagnostic tests could help improve early detection practices and management of dengue fever in Togo.